Transformation of Dolanan song in Kabupaten Trenggalek - Wiwik Andayani (Pascasarjana UM, 2014)
Transformasi Tembang Dolanan di Kabupaten TrenggalekAbstract: Dolanan song is a song sung by children while they are doing game activities. The lyric of dolanan song is part of oral folklore, as Java folk poetry that is sung by people. They are some transformations in the use and creation. This study tries to (1) describe the process of transformation of dolanan song, (2) find the pattern of transformation of dolanan song. The research is a qualitative study using etnopuitika. The data of this research are old dolanan song lyric and new dolanan song lyric. The techniques of data collection used for this study are documentation, interviews, and observation. The data analysis begin from form analysis, performance analysis, content analysis, until local colour analysis. The results are (1) the form transformation process: sound, diction,verse, stanza, and they are shown to be a form of appearance of the old songs to new songs, the comparasion of the two shapes of transformation pattern show the changer that eventually shape the form trans-formation, the content transformation process: the general meaning and messages from both old song and new song are coveyed, the comparasion of two shapes of transformation pattern show the changer that eventually shape the content transformation; (2) the pattern of form transformation: strengthening, continuing, modifying, deviating, and rejecting, the pattern of content transformation: strengthening, continuing, modifying, and deviating from convention.Key Words: transformation, dolanan song, form, content, java Abstrak: Tembang dolanan merupakan tembang yang dinyanyikan anak-anak yang disertai kegiatan permainan. Tuturannya digolongkan sebagai karya sastra berbentuk folklor lisan, berjenis puisi rakyat Jawa yang dinyanyikan. Penggunaan dan perkembangannya, mengalami transformasi. Penelitian ini bertujuan (1) mendeskripsikan proses transformasi tembang dolanan, (2) menemukan pola transformasi tembang dolanan. Penelitian ini merupakan penelitian kualitatif dengan rancangan etnopuitika. Data berupa tuturan tembang lama dan baru. Teknik pengumpulan data melalui studi dokumentasi, wawancara, dan observasi. Analisis data terdiri analisis bentuk, analisis pentas sastra, analisis isi, dan analisis warna budaya lokalnya. Hasil penelitian berupa temuan (1) proses tranformasi bentuk: bunyi, diksi, larik, bait, dan bentuk penampilan tembang lama dibandingkan dengan yang baru mem-bentuk pola transformasi bentuk, proses transformasi isi: makna secara umum dan pesan tembang lama dibandingkan dengan yang baru membentuk pola transformasi isi; (2) pola transformasi bentuk: menguatkan, meneruskan, mengubah, menyimpang dan menolak, pola transformasi isi: menguatkan, meneruskan, mengubah, dan menyimpang dari konvensi. Kata kunci: transformasi, tembang dolanan, bentuk, isi, jawa